Drug selection for inner ear therapy - Salt, Alec N.; Turner, Jeremy G. (Frontiers in Pharmacology, 2024)
One of the primary tenets in pharmacotherapy is that the applied drug must reach the target tissue at therapeutic concentration. For many therapies intended to treat hearing disorders it has become apparent that we have failed to achieve this goal, contributing to poor outcomes in several important clinical trials. The crux of the delivery problem is that small lipophilic molecules pass with relative ease through membranous boundaries of the body. This initially seems advantageous when the drug is applied intratympanically, enabling entry into perilymph through the round window membrane. Unfortunately, the same property also allows the drug to pass through endothelial cells of blood capillaries, allowing it to be eliminated from perilymph. Drugs that are eliminated rapidly as they diffuse along the cochlear scalae will only treat basal high-frequency cochlear regions and will not reach therapeutic concentrations in the apical regions of the human cochlea. In this study we have used the FluidSim program, a computer model of the inner ear fluids, to derive perilymph elimination properties for 15 molecules from published and archival data sets, which are compared with calculated molecular properties. Smaller, lipophilic drugs are shown to be eliminated from perilymph more rapidly, with half-times as fast as 17 min, compared to larger, polar ones, with half-times as long as 1304 min (21.7 hours). Based on their molecular properties' drugs can be identified that distribute well along the cochlea when applied intratympanically. This excludes many drugs that have been used for, or are currently in development for, inner ear therapy. On the other hand, it opens a vast array of less-studied, larger molecules, many of which would be unsuitable for oral delivery (characterized as "not druglike") but representing promising candidates for local inner ear therapy. In the earliest stages of consideration, drugs need to be selected based on the properties which govern their ability to reach the appropriate target site and not whether they are efficacious in small animals or have high potency in vitro. Confirmation that the selected drug is reaching the target site(s) in a large animal model should ideally precede expensive clinical trials.